Medicinal Chemistry and Pharmacological Potential of Fullerenes and Carbon Nanotubes - Cataldo, Franco.; Cataldo, Franco.; da Ros, Tatiana.; da Ros, Tatiana. (Carbon Materials: Chemistry and Physics, 2008)
Medicinal Chemistry and Pharmacological Potential of Fullerenes and Carbon Nanotubes features important insights into the applications of fullerenes and carbon nanotubes. It discusses the fullerene and nanotubes derivatives which are effective against viruses, cells, and bacteria and those which are able to interact and inhibit certain enzymes. Also covered in this book are the formation of complex structures between biologically active molecules and carbon materials. Furthermore, the application of fullerenes in certain medical therapies is explored, including the very recent discovery of new bio-compatible media which could be used as carriers in the delivery of fullerenes in vivo. An additional topic of this text is the formation of hybrids between nanotubes and biological molecules and their use as chemical sensors. Medicinal Chemistry and Pharmacological Potential of Fullerenes and Carbon Nanotubes will be a useful tool of reference for researchers, postgraduates and advanced undergraduates in the Chemical, Biomedical, and Materials sciences.